Maladaptive coping styles moderate the relationship between information on cancer treatment and psychosocial symptoms: an Italian multicenter study - Zerbinati, L.; Folesani, F.; Caruso, R.; Belvederi Murri, M.; Nanni, M.G.; Righetti, S.; Chiefari, L.; Muscettola, A.; Toffanin, T.; Costantini, A.; Zaccagnino, B.; Ruffilli, F.; et al. (Frontiers in Psychology, 2024)
Objectives. Disclosing information on diagnosis, prognosis and treatment is a delicate process in oncology, although awareness levels have over time increased in peoplewith cancer . However, individual characteristics should be considered when communicating difficult information.We conducted a multicentric study to explore the moderating role of coping styles on the relationship between information about cancer, quality of life and psychological distress.Methods. In the period between October 2015 and February 2016, 288 patients with a diagnosis of a solid tumor were recruited from seven Italian oncology units. All participants were administered the Distress Thermometer (DT), the Mini-Mental Adjustment to Cancer (Mini-MAC), the European Organization for Research and Treatment of Cancer (EORTC) Core Quality of Life Questionnaire (QLQ-C30), and the EORTC QLQ 25-item information module (INFO25). We explored the moderating effect of coping style with quality of life (QoL) and distress (DT) as dependent variables and information on cancer treatment as independent variable.Results. Low levels of anxious preoccupation significantly moderated the relationship between information on treatment and QoL (R2 6%, p < 0.001), while low and medium levels of hopelessness significantly moderated the relationship between information on treatment and DT (R2 = 14%, p = 0.033). Adaptive coping strategies, such as fighting spirit and fatalism, and borderline strategies such as avoidance, did not play a role in this relationship.Conclusions. Taking into account and evaluating coping mechanisms in cancer care is a priority when disclosing information on treatments, in order to tailor communication style to individual features.